Analisis Kestabilan Lubang Bukaan Pada Lubang D-12 Tambang Bawah Tanah Batubara Berdasarkan Metode RMR-System PT. Dasrat Sarana Arang Sejati, Parambahan, Kecamatan Talawi, Kota Sawahlunto, Sumatera Barat - Berryl Hannah; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2023)
This study aims to determine the rock mass class, support strength value, opening hole safety factor and support safety factor, as well as safe support recommendations based on rock class and support dimensions. Since the point in underground mining problems is usually related to the selection of supports and all underground mining activities are carried out by making openings, the opening holes are made by maintaining their stability to be safe for workers and mining equipment to be used and to ensure the safety of workers and the economic value of their use. In identifying the characteristics of the rock mass in an opening hole can be done by several methods. One of them is the geomechanical method (Rock Mass Rating System). This method will produce a rock mass class, rock strength, potential collapse, opening hole stability and get recommendations for a suitable support system based on the results of RMR ground support, and get the condition of the wooden support used. From the results of the analysis there are several parameters of the RMR method that have been carried out, in the D-12 Tunnel B hole for coal is in class III (fair rock) with an RMR of 59 with a Stand Up Time of 83 Days with a maximum width or length of 5 m without the help of support. And for silstone is in class II (good rock) with RMR of 64 and Stand Up Time is 354 days with a maximum width or length of 5 m without support. The value of the wood support safety factor is known, the actual FK cap has a value of 1.322 and the actual FK side post is 5.586, where the FK cap does not meet the safe requirements set out in KEPMEN 1827K/30 / MEM / 2018. Then after evaluating the support distance, the FK cap is obtained to be 1.5. Based on the safety factor, the recommendation for a good and safe buffer system for the company to use is with a wood diameter of 15 cm and a buffer distance of 1.61 m.